The Influence of Promotion, Price, Service Quality on Customer Satisfaction and Repurchase Decisions at Alfamart and Indomaret (Study at Alfamart and Indomaret in Banjar City) - Riyanto, Sugeng; Adhitya Rahmat Taufiq (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study uses 3 independent variables of promotion, price, and service quality, while the dependent variable is customer satisfaction and repurchase decisions. The sample of respondents consisted of 100 respondents, the sample was selected using survey and explanatory survey methods. The data analysis technique uses Smart PLS software version 2.0.m. From the research results it is known that customer satisfaction and repurchase decisions have a value of 0.422. Thus it can be seen that the variable customer satisfaction and repurchase decisions contribute to the promotion, price and service quality variables by 42%, while the remaining 58% is the contribution of other variables. The t test results show that promotion, service quality and repurchase decisions have a significant effect on customer satisfaction. Meanwhile, the price variable on customer satisfaction has no significant effect. The results of the F test indicate that there is an effect of promotion, price, service quality on customer satisfaction and repurchase decisions have a significant effect at Alfamart and Indomaret Kota Banjar.